MEMBANGUN MANAJEMEN MUTU PENDIDIKAN MENGHADAPI TANTANGAN GLOBAL - Yusuf, Musfirotun (IAIN Pekalongan, 2009)
Globalization is a condition in which the world experienced the dissemination of information, technology and its use with competition in a variety of activities for all people and nations. Therefore it is an obligation for every Indonesian human being to build quality. Quality management education itself in facing global challenges is not easy, but it will be reversed, if it is carried out jointly by various parties, especially the leadership who commit, has a vision for the future that is credible (credible because of the honesty and commitment to themselves and the institution), had a great effort to realize the vision and its mission, acceptability and accountability (received subordinates and be accountable for its leadership), conceptually skilled (mastering science and technology), social (able to hang out and have an extensive network or networking), and technical (to be more authoritative and is not fooled his subordinates).